2016
DOI: 10.1186/s12936-016-1591-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microRNAs expressed in the African malaria vector Anopheles funestus life stages using high throughput sequencing

Abstract: BackgroundOver the past several years, thousands of microRNAs (miRNAs) have been identified in the genomes of various insects through cloning and sequencing or even by computational prediction. However, the number of miRNAs identified in anopheline species is low and little is known about their role. The mosquito Anopheles funestus is one of the dominant malaria vectors in Africa, which infects and kills millions of people every year. Therefore, small RNA molecules isolated from the four life stages (eggs, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 95 publications
3
31
0
Order By: Relevance
“…Annotation of the sRNAs in the four libraries indicated that the most abundant class of sRNAs in the eggs, larvae, pupae and adult females’ libraries was miRNAs, rRNAs (larvae and pupae) and tRNAs respectively. This result is consistent with previous research in Anopheles funestus [ 37 ], indicating that protein synthesis during development is of great importance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Annotation of the sRNAs in the four libraries indicated that the most abundant class of sRNAs in the eggs, larvae, pupae and adult females’ libraries was miRNAs, rRNAs (larvae and pupae) and tRNAs respectively. This result is consistent with previous research in Anopheles funestus [ 37 ], indicating that protein synthesis during development is of great importance.…”
Section: Discussionsupporting
confidence: 93%
“…Novel miRNAs found in this study are not conserved in the Anopheles genus, and we cannot find homologs in other insect species by searching the miRBase, suggesting that these might be species-specific miRNAs. However, the predicted novel miRNAs exhibited much lower expression levels when compared with conserved miRNAs, which is also consistent with previous reports [ 9 , 37 ]. Previously, Dritsou and his colleagues [ 6 ] computationally predicted 115 miRNAs (after removing 33 duplicates and 11 putatively new miRNA, 71 left) in An.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…anthropophagus [ 32 ] and An . funestus , [ 54 ] respectively. ast-miR-2943 and ast-miR-2945 were highly expressed in An .…”
Section: Discussionmentioning
confidence: 99%
“…While mechanisms are known for how gene expression fluctuates during a blood meal at the transcriptional level (Attardo et al 2005), the mechanisms of post-transcriptional regulation of gene expression are largely unknown. As a much-needed step to address this gap in knowledge, the vector biology field is currently exploring post-transcriptional regulation of mRNA transcripts and its effects on female mosquito physiology by studying a class of small RNAs called microRNAs (miRNAs) (Mead and Tu 2008; Li et al 2009; Gu et al 2013; Hu et al 2015; Skalsky et al 2010; Biryukova et al 2014; Liu et al 2017; Jain et al 2014; Castellano et al 2015; Liu et al 2014b; Jain et al 2015; Allam et al 2016; Lampe and Levashina 2018; Fu et al 2017; Liu et al 2014a; Zhao et al 2017; Zhang et al 2016; Lucas et al 2015a; Lucas et al 2015b; Ling et al 2017; Zhang et al 2017; Akbari et al 2013).…”
mentioning
confidence: 99%